2018
DOI: 10.1108/ijlss-02-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the extent of Lean Six Sigma implementation in the West of Ireland

Abstract: Purpose The purpose of this paper is to explore the extent of Lean Six Sigma (LSS) implementation within manufacturing companies in the West of Ireland. It examines the key success and failure factors, benefits and quality tools influencing LSS projects deployment. Design/methodology/approach The study adopted a mixed research method (quantitative and qualitative approach). Research data were collected through a structured survey questionnaire to the target population followed by interview case studies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 49 publications
1
62
0
Order By: Relevance
“…Each Six Sigma project uses a structured and organised approach, led by a project methodology expert and involving a n a t i o n a l J o u r n a l o f Q u a l i t y & R e l i a b i l i t y M a n a g e m e team brought together for the purpose of the project (Anand et al, 2009;Margazão, Carvalho, 2015). The same is true for Lean Six Sigma improvement projects (Iyede, Fallon, Donnellan, 2018).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Each Six Sigma project uses a structured and organised approach, led by a project methodology expert and involving a n a t i o n a l J o u r n a l o f Q u a l i t y & R e l i a b i l i t y M a n a g e m e team brought together for the purpose of the project (Anand et al, 2009;Margazão, Carvalho, 2015). The same is true for Lean Six Sigma improvement projects (Iyede, Fallon, Donnellan, 2018).…”
mentioning
confidence: 77%
“…To guarantee the development of sustainable Lean Six Sigma projects, tools, techniques and methods should be properly used and in the correct order (Iyede, Fallon and Donnellan, 2018) (Antony and Gupta, 2018). The selection of the most appropriate tools from the toolbox as well as the methodologies and resources that best fit the problem are crucial to a good project result (Antony and Gupta, 2018;Henderson and Evans, 2000).…”
Section: Faulty Selection Of Process Improvement Methodology and Its mentioning
confidence: 99%
“…Previous work for a similar purpose used scales of different lengths. Surveys using five-point Likert scale were done by Alhuraish et al (2016), Antony and Banuelas (2002), Ismyrlis and Moschidis (2018), Iyede et al (2018), Kalra and Pant (2013), Khalili et al (2017), Kharub (2019), Soti et al (2010) and Stankalla et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…Using factor analysis, they reported top CSF under 6 factor-labels. Iyede et al (2018) reported CSF based on a survey of 43 samples, whereas Kalra and Pant (2013) used a sample of 48 Indian automotive organisations to reveal 8 CSF. Tyagi et al (2017) surveyed 307 enterprises to collect 27 CSF which was clubbed in 6-factor labels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concept of quality in education seems to be elusive and the scholars on the subject have defined it with different view of point. One definition of quality in education by the authors [6], [12], [13] stated that the quality in education "focusing on meeting a pre-defined set of standards, specifications, and requirements, or focusing on exceeding the highest standards in pursuit of excellence and exclusivity". Other definition by the authors [14]- [16] stated the quality in education can be defined as "focusing on accountability to the public or providing a transformative learning experience to benefit students and employers".…”
Section: Concept Of Quality In High Education Institutesmentioning
confidence: 99%